How can Democracy Survive? - Kux, Mathias Negrão (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2018)
In 2018, the Brazilian faces an important democratic process in the New Republic represented by the elections, which will define Brazil's course for the coming years. This article aims to propose solutions to solve or alleviate the theoretical and practical problems encountered in a democratic regime. For that, the methodological tools of the research center of the Austrian School were used, incorporating in the democratic institutions those elements present in the free market process that make it desirable. It has been shown how the proposed solutions make the democratic system more suitable to serve the interests of citizens.